2021
DOI: 10.3390/s21051632
|View full text |Cite
|
Sign up to set email alerts
|

Phthalocyanine-Functionalized Magnetic Silica Nanoparticles as Anion Chemosensors

Abstract: Anionic species are one of the most common pollutants in residual and freshwaters. The presence of anthropogenic anions in water drastically increases the toxicity to living beings. Here, we report the preparation of a new optical active material based on tri(tosylamino)phthalocyanines grafted to ferromagnetic silica nanoparticles for anion detection and removal. The new unsymmetrical phthalocyanines (Pcs) proved to be excellent chemosensors for several anions (AcO−, Br−, Cl−, CN−, F−, H2PO4−, HSO4−, NO2−, NO3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…The literature citation revealed that 2θ value of amorphous silica depends upon temperature treatment and water to tetraethoxysilane (TEOS) ratio. Our measured 2θ values of silica were found to analogous to the reported 2θ value of silica [61]. Further, the XRD studies of the APTES functionalized silica (9) and nano-composites (11) showed 2θ at 23 • only with increase in peak intensities confirmed the immobilization of APTES and organic ligand (3) on silica surface with confined amorphous character of silica.…”
Section: Transmission Electron Microscopy (Tem) Analysissupporting
confidence: 83%
“…The literature citation revealed that 2θ value of amorphous silica depends upon temperature treatment and water to tetraethoxysilane (TEOS) ratio. Our measured 2θ values of silica were found to analogous to the reported 2θ value of silica [61]. Further, the XRD studies of the APTES functionalized silica (9) and nano-composites (11) showed 2θ at 23 • only with increase in peak intensities confirmed the immobilization of APTES and organic ligand (3) on silica surface with confined amorphous character of silica.…”
Section: Transmission Electron Microscopy (Tem) Analysissupporting
confidence: 83%
“…As a consequence, it was depicted that the non-crystalline character of Stöber silica was remained intact even after modifications with APTES and organic moiety, showed that silica nanospheres were enough stable to conduct surface chemical reactions. However, the XRD peak intensities declined from silica to APTES@SiO 2 to SAN (6), illustrating that APTES and sulfonamide were sequentially immobilized over the silica particles [45].…”
Section: Powder X-ray Diffraction (Xrd) Studiesmentioning
confidence: 99%
“…Functionalized metalloporphyrins can interact with many different cations and anions, changing their structures and photophysical properties as a result. Fluorinated porphyrinoids have been developed as sensors due to their photophysical, electrochemical and molecular recognition properties (149,150,151,152,153). Cations like mercury(II) and lead(II) and anions like cyanide and arsenate are considered pollutants and serious environmental threats.…”
Section: Chemosensorsmentioning
confidence: 99%
“…Building on this chemosensor work as well as the same group’s previous work with magnetic nanoparticles, Rodrigues et al . investigated the functionalization of silica‐coated Fe 3 O 4 NPs with zinc phthalocyanines to serve as optical sensors for harmful anions (153). As with the previous studies (77,78), aminopropyl groups attached to the silica coating of the NP served as nucleophiles to substitute an asymmetric A3B‐type phthalocyanine.…”
Section: Biomedical Applicationsmentioning
confidence: 99%